Performance Characteristics and Blood Metabolites of Weaner Pigs Fed Different Feed Grade Coded MUSARPOMS - , V. E. Ekhorutomwen; , S. O. Nwokoro (Archives of Current Research International, 2023)
A new feed grade coded MUSARPOMS 25%, 50% and 75% at 10 and 20% replacement level was used as a case study to determine growth performance and blood metabolites of weaner pigs. Twelve weeks feeding trial was conducted to determine the performance and some haematological paremeters of weaner pigs fed MUSARPOMS diets as replacement for maize. Twenty eight six weeks’ old weaner pigs with an average weight of 8.00kg were randomly allocated to seven treatments of 0 (Control), 25%, 50% and 75% at 10 and 20% replacement levels of MUSARPOMS 25% Grade (25% ripe plantain peels and 75% Palm oil mill slurry mixture), MUSARPOMS 50% Grade (50% ripe plantain peels and 50% Palm oil mill slurry mixture), and MUSARPOMS 75% Grade (75% ripe plantain peels and 25% Palm oil mill slurry mixture). Each treatment had four replicate made up of two male and two female. Data were collected on live weight, weight gained and feed intake while feed efficiency and feed conversion ratio were determined. The average initial weight, final live weight, total weight gained and daily weight gained showed no significant (P > 0.05) differences in growing pigs across the treatments. Feed conversion ratio and feed efficiency did not differ significantly (P>0.05) from the control. Some haematological parameters, fasting blood sugar and serum protein were tested for each 28 growing pigs at the end of the feeding experiment. Results of the full blood count revealed that the white blood cells and its differentials showed no significant (P<0.05) differences except monocyte. Serum protein and glucose showed no significance (P>0.05) differences in globulin, total protein and glucose. Based on the results of this experiment, it can be concluded that feeding “MUSARPOMS” grades at 10% and 20% levels compared well with the conventional energy feedstuff. The growth performance of the pigs indicated adequate utilization of the three MUSARPOMS grades developed.